Cardio-pericardial wounds - Praderi, José; Carriquiry, Guillermo; Pomi, Jorge; Ríos, Guaymirán; Lerena, Ana (Cirugía del Uruguay, 1991)
Between June 1986 and June 1989 five patients were admitted into the Po/ice Hospital Emergency Department because of cardiopericardial injuries: three due to knife, one due to firearm and one due to closed thoracic traumatism. The main clinical presentation was cardiac tamponade in one case, shock due to acute hypovolemia in two cases, and combined conditions in the other two.